The Agentic Ways Children, Their Families and Their Community Sustain Participation in Occupations in the Context of Poverty - Leadley, Simon; Hocking, Clare; Jones, Margaret (Elsevier, 2026)
There is considerable evidence that children in poverty and their parent/s and communities are agentic in coping with poverty; however, there is limited research addressing how they overcome poverty-related obstacles to participation in everyday activities (occupations) that support their health, wellbeing, and future potential. We employed Lister’s framework of ‘Getting by’, ‘Getting (back) at’, ‘Getting out’, and ‘Getting organised’ to analyse data generated from a study (n = 25) conducted in 2022 with children aged 10–13 years, their families, and community organisations in a city in Aotearoa New Zealand. The study used a qualitative case study approach, incorporating multiple data collection methods, rigorous analysis, cultural guidance, and ethical approval. Findings revealed that children’s agency is situational. Children living in poverty exercised agency to overcome context–specific barriers to participation within the constraints of parental boundaries set for safety, availability of resources, and occupational opportunities, while sustaining aspirations for future participation. Their agency was shaped by values and skills taught by parent/s and extended family, and by involvement in available occupations. Social services such as schools and community organisations supported children’s agency, though this support diminished with age. Interpreting children’s agency from a transactional perspective highlights its contextual nature, recognising children’s dependence on social actors to build occupational capabilities that may lift them out of poverty, even as their personal aspirations and agentic actions remain clear. Despite these efforts, access to occupational opportunities and sustainable, government-backed support for community-led initiatives remains limited.
Keywords: 4409 Social Work; 4410 Sociology; 44 Human Society; Pediatric Research Initiative; Generic health relevance; 1 No Poverty; 1402 Applied Economics; 1607 Social Work; Poverty; Children; Families; Community; Agency; Participation in Occupations